Readings in society and religion of medieval south india - P. Chenna Reddy (New Delhi : Research India Press, 2006)
"Readings in Society and Religions of Medieval South India," edited by P. Chenna Reddy, is a compilation of scholarly papers presented at a national seminar, offering a multifaceted exploration of the socio-religious landscape of medieval South India, particularly Andhra Pradesh. The volume meticulously examines the intricate interplay between religious beliefs, social structures, and cultural practices, highlighting the significant transformations that occurred during this period. By arranging well-researched papers chronologically and geographically, the book provides a comprehensive understanding of the evolving religious fabric and its profound impact on societal harmony. This collection serves as a valuable resource for historians, religious scholars, philosophers, students, and general readers interested in the socio-cultural dynamics of medieval South India.
Includes index.
Keywords: Medieval south India : social history; Medieval south India: religious history; History of Andhra Pradesh in the medieval period; Religion and society in south India; Socio Cultural aspects of India in the medieval period